Empirical prescribing of penicillin G/V reduces risk of readmission of hospitalized patients with community-acquired pneumonia in Norway: a retrospective observational study - Høgli, June Utnes; Garcia, Beate Hennie; Svendsen, Kristian; Skogen, Vegard; Småbrekke, Lars (BMC Pulmonary Medicine, 2020)
Background - Norwegian guideline recommendations on first-line empirical antibiotic prescribing in hospitalised patients with community-acquired pneumonia (CAP) are penicillin G/V in monotherapy, or penicillin G in combination with gentamicin (or cefotaxime) in severely ill patients. The aim of this study was to explore how different empirical antibiotic treatments impact on length of hospital stay (LOS) and 30-day hospital readmission. A secondary aim was to describe median intravenous- and total treatment duration. Methods - We included CAP patients (≥18 years age) hospitalised in North Norway during 2010 and 2012 in a retrospective study. Patients with negative chest x-ray, malignancies or immunosuppression or frequent readmissions were excluded. We collected data on patient characteristics, empirical antibiotic prescribing, treatment duration and clinical outcomes from electronic patient records and the hospital administrative system. We used directed acyclic graphs for statistical model selection, and analysed data with mulitvariable logistic and linear regression. Results - We included 651 patients. Median age was 77 years [IQR; 64–84] and 46.5% were female. Median LOS was 4 days [IQR; 3–6], 30-day readmission rate was 14.4% and 30-day mortality rate was 6.9%. Penicillin G/V were empirically prescribed in monotherapy in 51.5% of patients, penicillin G and gentamicin in combination in 22.9% and other antibiotics in 25.6% of patients. Prescribing other antibiotics than penicillin G/V monotherapy was associated with increased risk of readmission [OR 1.9, 95% CI; 1.08–3.42]. Empirical antibiotic prescribing was not associated with LOS. Median intravenous- and total treatment duration was 3.0 [IQR; 2–5] and 11.0 [IQR; 9.8–13] days. Conclusions - Our findings show that empirical prescribing with penicillin G/V in monotherapy in hospitalised non-severe CAP-patients, without complicating factors such as malignancy, immunosuppression and frequent readmission, is associated with lower risk of 30-day readmission ...